Respon Pemberian Pupuk Organik Cendawan Mikoriza Arbaskular (CMA) dan Beberapa Varietas Terhadap Produksi Jagung Manis (Zea mays L.) - Elli Afrida; Lisdayani Lisdayani; Anwar Habibi (Jurnal Agrotek Lestari, 2025)
Sweet corn plants have good prospects for cultivation, because they have a higher selling price than ordinary corn and have a relatively short production life. To meet the increasing demand, farmers need to make efforts to improve good cultivation systems. Among them are empowering the use of organic materials. The purpose of the study was to determine the response of CMA fertilizer and varieties to sweet corn plant production. This study was conducted at the UNIVA agricultural land on Jalan Simalingkar B Medan. This study was conducted from April to July 2024. This study used a factorial randomized block design consisting of two factors, namely: Factor 1, CMA fertilizer consists of 45 levels, namely: C0 = control, C1 = Liquid fertilizer dose 5 ml / liter, W2 = Liquid fertilizer dose 10 ml / liter, W3 = Liquid fertilizer dose 15 ml / liter, W4 = CMA fertilizer dose 30 gr / plant, C2 = CMA dose 60 gr / plant, and C3 = CMA dose 60 gr / plant. Factor 2The second factor is the variety consisting of 4 levels, namely: V1 = Secada, V2 = Panglima, V3 = Sweet boy, V4 = Bonanza F1. The results of the study showed that the use of CMA fertilizer was significantly different from the gross weight of production per sample and the net weight of production per sample. The best treatment was C3 with a dose of 90 grams / plant. The use of varieties was significantly different from the gross weight of production per sample and the net weight of production per sample, the best variety was V4, namely the Bonanza F1 variety.Keywords: Sweet Corn, biofertilizer, Varieties